Mapeo del talento empresarial: Modelo híbrido basado en la intergración de la matriz nine box y el método multicriterio TOPSIS; Organizational talent mapping: A hybrid model integrating the nine-box matrix and the TOPSIS multicriteria method - Sofia Carla Cortaberria; Miguel Angel Curchod (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2025)
– Talent management is a strategic function, and its objectives are to attract, develop and retain talented employees at different levels of the organization. One of its practices is to have a talent map allowing a general view of the availability in the company. The aim of this work is to present a hybrid model for talent mapping, based on the integration of the Nine Box matrix and the multicriteria method TOPSIS, to improve decision-making in talent management.The nine-box matrix provides visual information about talent, using performance and potential as axes. This tool provides abundant information; however, it is insufficient to make decisions within the same category. For this reason, the evaluation process was integrated by applying TOPSIS, which allows for addressing problem resolution with multiple alternatives considering various criteria. The method produces a ranking of employees, providing valuable information for analysis and decision-making within each box.Once both tools are integrated, it is concluded that the methodologies provide complementary information. The matrix groups employees into each box, while TOPSIS facilitates specific decisions by helping to prioritize within the same box.We recommend the integrated use of both methods as it is effective in managing the complexity of talent management decisions.To the best of our knowledge, this is one of the first applications combining both tools for talent management in service-oriented companies in Argentina.
Keywords: C02; C44; D81; I13; 330; Multicriteria decision support; TOPSIS method; Nine box matrix; Talent mapping; Talent